On the application of the multistage Laplace Adomian decomposition method to the chaotic Chen system - Ajibola, Saheed O.; Kolebaje, Olusola Tosin; Sedara, Samuel O. (International Journal of Applied Mathematical Research, 2013)
In this paper, Laplace Adomian Decomposition Method (LADM) and the Multistage Laplace Adomian Decomposition Method (MLADM) were applied to obtain solutions to the Chen system for the non-chaotic and chaotic case. The study shows that the LADM only gives reliable results for t <<1. Comparison between the MLADM and the classical fourth-order Runge-Kutta (RK4) solutions shows that the MLADM performs well with high accuracy. The study shows that MLADM is a powerful and promising tool for solving nonlinear systems of ODEs of chaotic and non-chaotic nature.